Migration, Education and Employment Pathways to Successful Integration - Teräs, Marianne; Osman, Ali; Eliasson, Eva (Education, Equity, Economy, 2024)
This is an open access book which focuses on different aspects of education, employment, and successful integration of migrants in three countries: Norway, Sweden, and Switzerland. The chapters in this book reflect on these issues from micro, meso and macro perspectives; some are based on interviews with migrants and people who work with them, others on documents and literature about migration. There are different pathways for skilled migrants to vocations. Some start working in their previous vocations after arriving in the new environment. Some re-enter their professions but on a lower level. Some can re-train themselves in a new vocation, and some will go to further education, as studies in different chapters of this book suggest. Common for successful integration seems to be several intertwined factors: the target language competence, strong motivation and agency, supporting networks and supporting persons, as well as structural opportunities of the new environment. The book's editorial board takes an eclectic view, hoping to start an academic debate about what 'successful integration' means. While discussions about the integration of migrants tend to focus on integration failures, there are millions of migrants, in different countries, who have successfully integrated into their new societies.